The Effectiveness of Executing a Personal Guarantee as Security in Resolving Non-Performing Loans in Indonesia - Frederick Septian Tuwan; Ariawan Gunadi (Lambung Mangkurat Law Journal, 2025)
This study aims to analyze the effectiveness of executing personal guarantees as security in resolving non-performing loans in Indonesia. The method used is normative legal research with a statutory and case study approach. In banking practice, personal guarantees are often used as additional security for credit facilities, yet their enforcement faces various legal and administrative challenges. One major issue is the absence of preferential rights for creditors in this guarantee, requiring banks to undergo litigation to execute the guarantor's assets. Furthermore, guarantors often transfer their assets to evade liability, complicating the execution process. The execution procedure also entails lengthy legal steps, including summons, lawsuits, and court rulings before enforcement. Therefore, clearer regulations and more effective execution mechanisms are needed to enhance legal certainty for both creditors and debtors.